AB0456 Comparative Study of Risk Factors for Venous and Arterial Thrombosis in Carriers of Antiphospholipid Antibodies. (15th July 2016) - Les, I.; Vidal, C.J.; Anaut, P.; Sánchez, C.; Andía, A.
Abstract : Background: Previous studies on factors predicting thrombosis in antiphospholipid syndrome (APS) show that vascular risk factors impact mainly on arterial thrombosis, while antiphospholipid antibodies (aPL) exert more influence on pure vein thrombosis or mixed thrombosis (venous and arterial). Objectives: To investigate and compare factors associated with occurrence of venous and arterial thrombosis in carriers of aPL. Methods: Prospective observational study of a cohort of patients with medium-high titers of aPL according to current recommendations on APS, enrolled in the outpatient clinic of a tertiary care hospital. Association between venous or arterial thrombosis and several factors such as age, sex, arterial hypertension, hypercholesterolemia, diabetes mellitus, smoking, obesity, oral contraceptives, platelet count, mean platelet volume (MPV), lupus anticoagulant (LA), IgG/IgM anticardiolipin antibodies (aCL), IgG/IgM anti-β2-glycoprotein I and partial aPL-score was assessed by univariate analysis (Pearson's X 2 and Fischer exact tests if qualitative variables, T -student and U Mann Withney tests if quantitative variables), following by a logistic regression. Results: Seventy-one patients (50 females, baseline age 51±17 years), of which 40 fulfilled definite classification criteria for APS (29 primary APS, 11 secondary APS), were followed for 4.2±4 years. Thirty-two patients developed 46 thromboses (24 in venous bed, 22 in arterial bed), of which 14 were recurrences. In univariate analysis, patients with venous thrombosis showed a higher prevalence of diabetes mellitus (3/5 vs 15/66, p=0.06) and LA (14/40 vs 4/31, p=0.05) and a lower platelet count (134.8±71.0 vs 168.1±73.3x10 3 /mm 3, p=0.09), whereas patients with arterial thrombosis were more frequently men (8/20 vs 9/51, p=0.04) of advanced age (59±14 vs 50±15 years, p=0.04), and had a higher prevalence of diabetes mellitus (3/5 vs 14/66, p=0.08) and higher levels of IgG aCL (72.7±122.2 vs 34.8±58.2 GPL, p=0.08) and MPV (10.8±2.0 vs 9.8±1.3 fL, p=0.02). The logistic regression identified male sex, age, diabetes mellitus and IgG aCL as predictors of arterial thrombosis, while positivity to LA as the only predictor of venous thrombosis (Table 1 ). Conclusions: In carriers of aPL, vascular risk factors such as male sex, age and diabetes predispose to arterial thrombosis together with IgG aCL, while the presence of LA is more specific of patients who experience venous thrombosis. References: Toloza SM et al. Systemic lupus erythematosus in a multiethnic US cohort (LUMINA). XXIII. Baseline predictors of vascular events. Arthritis Rheum 2004. Danowski A et al. Determinants of risk for venous and arterial thrombosis in primary antiphospholipid syndrome and in antiphospholipid syndrome with systemic lupus erythematosus. J Rheumatol 2009. Calvo-Alén J et al. Systemic lupus erythematosus in a multiethnic US cohort (LUMINA). XXV. Smoking, older age, disease activity, lupus anticoagulant, and glucocorticoid dose as risk factors for the occurrence of venous thrombosis in lupus patients. Arthritis Rheum 2005. Disclosure of Interest: None declared